Comparative Analysis of Nominal Analytical Reduplicatives in the English and Armenian Languages - KARAPETYAN, SIRARPI (Bulletin of Yerevan University B: Philology, 2021)
The article deals with the structural and semantic peculiarities of nominal analytical reduplicatives in the Armenian and English languages. The aim of the article is to reveal the similarities and differences in the mentioned word-formation constructions and to analyse the components of these words from morphological-categorial (to which part of speech they belong) point of view. The article also deals with the semantic differences between the corresponding word-fomation units in the given two languages. The peculiarities revealed have important significance to the structural and typological characterization of the languages under study.
Keywords: word-building, analytical reduplicatives, sound interchange, compounding, pattern, component, semantic field